Disentangling Business- and Tax-Motivated Bilateral Royalty Flows - Arjan Lejour; Maarten van 't Riet (Center for Economic Studies and ifo Institute (CESifo), 2023)
Shifting intellectual property (IP) rights across jurisdictions is a well-known strategy of multinationals to reduce corporate income taxation. We investigate the extent to which the flows of remunerations for the use of IP rights are affected by differences in corporate income and withholding taxation. Using OECD data between 2014 and 2019, we determine the influence of bilateral tax rates on the IP-location. These rates result from a network analysis that distinguishes between the potential gains from direct shifting of IP rights and treaty shopping. The latter are gains for multinationals from exploiting lower withholding taxes by routing royalty flows through conduit countries. We use these bilateral tax gains to isolate the flows that could be only business-motivated. Next we apply a gravity framework with PPML estimators. We estimate that at least 18% of the royalty flows is motivated by tax planning in this period, which reduces tax revenues by 6.5 to 16 billion US dollar in 2018. We argue that both estimates are lower bounds due to missing observations. More reporting by OECD countries of flows to and from tax havens would improve the precision of the estimates. To the best of our knowledge these are the first estimates of worldwide tax avoidance with royalties.
Keywords: H25; H26; H32; 330; bilateral royalty flows; international tax avoidance; treaty shopping; withholding tax; tax havens